Intestinal Stomas—Postoperative Stoma Care and Peristomal Skin Complications - Steinhagen, Emily; Colwell, Janice; Cannon, Lisa M. (Clinics in Colon and Rectal Surgery, 2017)
Intestinal stomas are necessary for several colon and rectal conditions and represent a major change in the new ostomate's daily life. Though dehydration is the most frequent etiology requiring readmission, irritant contact dermatitis and a host of other peristomal skin conditions are more common complications for ostomates. Wound, ostomy, and continence nurses are invaluable resources to both ostomy patients and providers. A few simple interventions can prevent or resolve most common peristomal complications. Good stoma care is possible in a resource-poor environment.
Keywords: ileostomy; colostomy; peristomal skin complications; enterostomal therapy; ostomy